Punishing unfairness: Rewarding or the organization of a reactively aggressive response?. Issue 5 (19th July 2013) - White, Stuart F.; Brislin, Sarah J.; Sinclair, Stephen; Blair, James R.
Objectives The neural correlates of human cooperative behavior remain poorly understood. Previous work has suggested that increases in striatal activation while punishing unfair offers represents reward signaling. However, other regions are also implicated when punishing others, for example dorsomedial frontal cortex (dmFC), anterior insula cortex (AIC), and periaqueductal gray (PAG). Moreover, the response of other regions implicated in signaling reward, for example ventromedial prefrontal cortex (vmPFC) or posterior cingulate cortex (PCC), has not been systematically examined. Experimental Design: Functional magnetic resonance imaging utilizing parametric modulation was conducted on 21 healthy adults participating in a social exchange paradigm. Principal Observations: Participants showed significant positive modulation of activity as a function of delivered punishment in caudate, dmFC, AIC, and PAG; that is, higher punishments by participants of unsatisfactory offers were associated with increasing activity within these regions. However, participants showed significant negative modulation of activity as a function of delivered punishment in vmPFC and PCC; increases in punishment level by participants were associated with decreases in activity within these regions. Conclusions: The current data question whether caudate activity when punishing unfair offers should be considered to indicate the reward value of this punishment. Instead, this activity, in conjunction with activity within dmFC, AIC, and PAG, may represent the organization of an untypical, punishing response that represents a reactive aggressive response to provocation. Notably, an inverse, regulatory relationship between vmPFC and PAG activity has been previously implicated in the context of another stimulus for reactive aggression; looming threat (Mobbs et al. [2007]: Science 317:1079–1083). Hum Brain Mapp 35:2137–2147, 2014. © 2013 Wiley Periodicals, Inc.